2006
DOI: 10.1128/aem.02706-05
|View full text |Cite
|
Sign up to set email alerts
|

Internally Controlled Real-Time PCR Method for Quantitative Species-Specific Detection and vapA Genotyping of Rhodococcus equi

Abstract: We developed a novel quantitative real-time PCR (Q-PCR) method for the soil actinomycete Rhodococcus equi, an important horse pathogen and emerging human pathogen. Species-specific quantification was achieved by targeting the chromosomal monocopy gene choE, universally conserved in R. equi. The choE Q-PCR included an internal amplification control (IAC) for identification of false negatives. A second Q-PCR targeted the virulence plasmid gene vapA, carried by most horse isolates but infrequently found in isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
(69 reference statements)
4
33
0
1
Order By: Relevance
“…The linearity of calibration curves represented by the regression coefficient (R 2 ) showed values close to 1 (p40, 0.9921; p40-IAC, 0.9931), indicating that the assay was highly linear. These results are similar to those for other Q-PCR methods used for other bacterial and eukaryotic organisms (10,(19)(20)(21)23).…”
Section: Capri M Mycoides Subsp Mycoides Lc and M Putrefaciens)supporting
confidence: 79%
“…The linearity of calibration curves represented by the regression coefficient (R 2 ) showed values close to 1 (p40, 0.9921; p40-IAC, 0.9931), indicating that the assay was highly linear. These results are similar to those for other Q-PCR methods used for other bacterial and eukaryotic organisms (10,(19)(20)(21)23).…”
Section: Capri M Mycoides Subsp Mycoides Lc and M Putrefaciens)supporting
confidence: 79%
“…Standard curves for the five Q-PCR assays developed in this study were constructed (not shown). The limit of detection, corresponding to the smallest amount of template DNA resulting in positive amplification in all replicates (35,40,46), for B. atrophaeus genomic DNA using the ITS and recA Ba Q-PCR assays was 7.5 fg per PCR (2 genome equivalents). The limits of detection of S. marcescens genomic DNA using gyrB, wzm, and recA Sm Q-PCR assays were 7.5 fg (1 genome equivalent), 75 fg (13 genome equivalents), and 7.…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods are not useful for human isolates, because they generally do not carry vapA-type virulence plasmids but alternative types, like the pig-associated vapB plasmid and a recently identified new bovine type, or are plasmid-less (16). We therefore developed a PCR method for species-specific R. equi identification based on the amplification of the choE gene (11,20), a chromosomal locus encoding a secreted cholesterol oxidase (14). ChoE is the cytolytic factor responsible for the synergistic hemolysis (CAMP-like) reaction elicited by R. equi in the presence of sphingomyelinase C-producing bacteria, such as Listeria ivanovii, Bacillus cereus, and Staphylococcus aureus (14).…”
mentioning
confidence: 99%